The Influence of Islamic Brand Image, Product Innovation, and Online Shopping Experience on Consumer Loyalty: The Intervening Role of Customer Satisfaction - Alviyatuz Zahiroh; Maksum Maksum (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The development of the halal cosmetics industry is rapidly growing, especially among students as active consumers of Wardah products. The proposed study will examine how the Islamic brand image, product innovation, and online shopping experience affect consumer loyalty using customer satisfaction as an intervening variable. This research uses a quantitative approach with a sample size of 96 respondents selected using a purposive sampling technique. The Structural Equation Modeling (SEM-PLS) method was used to analyze the data with the help of the Partial Least Squares algorithm. The findings of the research indicate that product innovation is a major factor that influences customer satisfaction, but the Islamic brand image and online shopping experience are not major factors in influencing customer satisfaction. Additionally, customer satisfaction is an important factor in consumer loyalty and can mediate the effects of all independent variables on consumer loyalty.